Semi-Strong Efficient Market Hypothesis in Dividend Announcements on the IDX - Ningrum, Mersa Lestari; Risman, Asep (Universitas Mercu Buana, 2022)
This research examines the semi-strong form of the market efficiency hypothesis in the context of dividend announcements on the Indonesia Stock Exchange (IDX), specifically good news in the form of an increase in dividend value over the previous year and bad news in the form of a decrease in dividend value over the previous year. This research aimed to see how dividend announcements affect stock prices and how efficient the market reaction is. The samples used in this study are the companies listed on the mainboard with a cash dividend payment policy once a year and consistently distribute dividends in a row in 2020 and 2021. The observation method used in this study is non-participatory. The return anomaly of up to 59 sample companies was used, with a 21-day observation period. One statistically significant event occurred when dividend announcements increased, and three statistically significant events occurred when dividend announcements dropped, according to the data processing results by t-test. It demonstrates that the market is efficient and supports the market efficiency hypothesis in its semi-strong form.